Determinants of risk sharing via exports: trade openness and specialisation. (4th August 2020) - Balli, Faruk; Pierucci, Eleonora; Gan, Jian
Economic theory predicts that one of the main benefits of financial globalisation is the improvement of international risk sharing. In this paper, we provide an empirical evaluation of the determinants of risk sharing via exports. We conclude that risk sharing via exports is somehow important in emerging countries but not among OECD countries. More importantly, we find that trade openness and production/export specialisation generally have, with some exceptions, positive and statistically significant relationship with risk sharing. On the contrary, concentration on export destinations has been proved to be negatively correlated with risk sharing.